A magnetic resonance imaging and gut flora-based study of intake desire in overweight/obese type 2 diabetes mellitus patients - Gao, Mingxuan; Gong, Liya; Zeng, Yanmei; Li, Dongling; Wen, Junyan; Guo, Ying; Li, Zhujia; Luo, Jingwen; Chen, Chunling; Wen, Ge (Frontiers in Neuroscience, 2025)
BackgroundAbnormal regulation of food intake in overweight/obese type 2 diabetes mellitus (T2DM) patients is an important cause of energy intake imbalance, and studies have demonstrated that the “gut-brain axis” is involved in a wide range of metabolic regulation through neural and endocrine processes, which has become a key breakthrough in revealing the abnormalities of food intake behaviors in T2DM patients.ObjectiveExploring the mechanism of action of abnormal regulation of ingestive desire in overweight/obese T2DM patients by integrating multimodal MRI techniques with microbiological analysis based on the gut-brain axis.MethodsThirty-one patients with overweight/obese type 2 diabetes mellitus (Group A), 17 patients with simple obesity with abnormal glucose metabolism (Group B), and 14 patients with simple obesity with normal glucose metabolism (Group C) were recruited, and clinical data, MRI, and stool specimens were collected to analyze the correlation between the imaging indicators and the intestinal flora, and clinical data.ResultsCompared with Group C, the abundance of Prevotella and Bifidobacterium in Group A and Group B was significantly reduced, while the abundance of Bacteroides, Fusobacterium, and Phascolarctobacterium was significantly increased. Meanwhile, in Group A and Group B, and Bifidobacterium were negatively correlated with HbA1c, thirst score, and FC values of the left supraoccipital gyrus and bilateral thalamus in the population with abnormal glucose metabolism; Bacteroides were negatively correlated with ALFF values of the right inferior frontal gyrus capitellum, and positively correlated with FC values of the left supraoccipital gyrus and bilateral thalamus, and so on.ConclusionAbnormal desire to ingest is the result of functional changes in brain regions, dysregulation of flora metabolism and neuroimmune interactions, providing a theoretical basis for clinical diagnosis and treatment targeting the gut-brain axis.